2010
DOI: 10.1007/s12161-010-9138-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Nitrite/Nitrate in Food Stuff Samples Using 2-Aminobenzoic Acid as a New Amine in Diazocoupling Reaction

Abstract: 2-Aminobenzoic acid has been used as an amine in diazocoupling reaction to form an azo dye in the quantification of nitrite/nitrate at trace level. The formed azo dye has an absorption maximum at 550 nm in aqueous phase, and the resulted dye can be extracted into organic solvent to lower the detection limit. The method obeys Beer's law in the concentration range 0-10 µg of nitrite in 25 ml of aqueous solution with a molar absorptivity of 3.6×10 3 L mol −1 cm −1 and 0-2 µg of nitrite in 5 ml of organic phase. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Stoikiometri antara PABA dan NEDA tercapai pada fraksi mol NEDA 0,5 atau saat perbandingan mol PABA dan NEDA yaitu 1 : 1 (Gambar 3). Mekanisme reaksi diazotasi menggunakan PABA dan NEDA berdasarkan perbandingan mol yang diperoleh disajikan pada Gambar 4 (Tsikas, 2007;Pandurangappa dan Venkataramanappa, 2011).…”
Section: Hasil Dan Pembahasanunclassified
“…Stoikiometri antara PABA dan NEDA tercapai pada fraksi mol NEDA 0,5 atau saat perbandingan mol PABA dan NEDA yaitu 1 : 1 (Gambar 3). Mekanisme reaksi diazotasi menggunakan PABA dan NEDA berdasarkan perbandingan mol yang diperoleh disajikan pada Gambar 4 (Tsikas, 2007;Pandurangappa dan Venkataramanappa, 2011).…”
Section: Hasil Dan Pembahasanunclassified
“…The detection limit for peroxynitrous acid/nitrite (S/N = 3) was 0.6 μM. However, the standard spectrophotometric methods showed that the linear range for nitrite is 1.2−5.8 μM and the detection limit was ∼1.0 μM, 42,43 indicating that the proposed method exhibited a high sensitivity and a wide dynamic range. The relative standard deviation (RSD) for nine repeated measurements of 0.01 mM peroxynitrous acid/nitrite was 2.5%.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…). NED has been long used for the chromogenic derivatization of compounds having nitrogen atoms . Until now, NED has only been used as an internal standard in CE .…”
Section: Introductionmentioning
confidence: 99%